Foreign direct investment - domestic investment nexus: Evidence from India - Abraham Babu (Contemporary Economics, 2021)
The relationship between foreign direct investment and domestic investment is intriguing. An important question arises - does foreign direct investment crowd in or crowd out domestic investment? This paper examines this nexus in the post-1991 period in India, which is also considered as the post-reform period. It is during this era; the above-mentioned topic gains more impetus as the economy opened up for further foreign inflows. The time period taken for the paper was from 1990-91 to 2014-15. The data series were checked for stationarity and the presence of long run relationship between foreign direct investment and domestic investment was analysed using cointegration test. Thereafter, the vector error correction model was estimated. The results clearly show that foreign direct investment crowds out domestic investment in India in the post reform period. The findings have significant policy implications because there is a substituting relationship between foreign direct investment and domestic investment in India.
Keywords: F21; E22; C32; 330; Foreign direct investment; domestic Investment; stationarity; cointegration; vector error correction model